Marketing strategy in creating the competitiveness of Ngudi Waluyo University (Perspective strategic management michael porter’s) - Abdul Aziz (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2022)
Business competition which is getting tougher in the era of globalization makes every company have to be able to compete and determine the right marketing strategy. Marketing aims to build and retain customers who can benefit the company. A good company image will influence people's thinking about a quality. So that the image is positive for the existence of the company and has an impact on the loyalty of consumers who use the company's services and products. This study aims to determine the effect of marketing strategies on brand image in influencing the interest of the learning community at Ngudi Waluyo University. The method used is quantitative analysis with multiple regression analysis techniques and for the sample obtained as many as 107 respondents with purposive random sampling technique. The results of the simultaneous analysis of marketing strategies consisting of three variables mediated by brand image have a significant effect on consumer interest. To maintain a good brand image in the company, it is necessary to carry out active marketing activities to maintain public trust and interest in studying at UNW.